Process of liquid supply to heated surface by a honeycomb porous plate for critical heat flux enhancement - Mt Aznam, Suazlan; Maruoka, Naru; Imai, Ryosuke; Mori, Shoji (The Japan Society of Mechanical Engineers and The Heat Transfer Society of Japan, 2021)
Various surface modifications controlling wettability and wickability have effectively enhanced the critical heat flux (CHF) in saturated pool boiling. Among them, this paper focuses on the CHF enhancement using a honeycomb porous plate (HPP). The HPP, which is commercially available, was generally used to filter exhaust gases from combustion engines, and has micron-order pores and millimeter-order holes which is called as a “cell”. Once an HPP was installed on the heated surface, the CHF in saturated pool boiling of water was improved more than approximately three times compared with a bare surface. The enhancement may be caused by: (1) the liquid supply due to capillarity, (2) liquid flowing down through the cells of an HPP due to gravity onto the heated surface, and (3) the release of vapor generated through the cells. However, the liquid supply process to heated surface due to (1) and (2) has not been clarified yet. Therefore, it is necessary to elucidate the detailed liquid supply mechanism for further CHF enhancement. In the present paper, two separate sets of experiments have been designed to investigate the liquid supply effect to the heated surface independently, namely, (1) automatic liquid supply due to capillary action by the porous part and (2) bulk liquid flowing down through the cells of an HPP. In summary, the measured values from the experiment extracting the liquid supply due to capillarity were in good agreement with the proposed capillary limit model. Moreover, for the high heat flux region (more than 3.5 MW/m2), the liquid supply due to the capillary force is dominant in enhancing the CHF. It was concluded that the keys to further CHF enhancement were the promotion of gas-liquid circulation based on the capillary limit model and improvement of wickability of the heated surface.